Shaping the aspirational healthcare system: undergraduate exposure in South Africa and the role of global surgery - Francis, Peace (Division of General Surgery, 2025)
Global Surgery is a burgeoning field especially in the low-and-middle-income country (LMIC) context. While exposure is increasing, research shows students are often exposed incidentally and not through the formal curriculum. Research also shows that there is no coherent pedagogy around Global Surgery education. In this qualitative, phenomenological study, nine final and penultimate year medical students were interviewed in semi-structured interviews to unpack their understanding of and exposure to Global Surgery. Five themes were extracted from the data – understanding of global surgery and its principles, undergraduate exposure to global surgery, benefits of global surgery, perceived flaws related to global surgery and roles for medical students in global surgery. Participants in this study had a systemic understanding of Global Surgery – they identified clear benefits of Global Surgery including its ability to strengthen health systems through multidisciplinary approaches. Participants also spoke to a lack of Global Surgery exposure in formal curriculum despite seeing many contextual benefits of exposure. As a new field we see the current lack of exposure and lack of established pedagogy as an opportunity for LMICs to define a Global Surgery pedagogy that can shape an aspirational healthcare system.